APPLICATION OF WATER QUALITY INDEX (WQI) FOR THE ASSESSMENT OF EGBE RESERVOIR - Oyewumi, Johnson; Adekitan, Adetoun; Adewumi, Emmanuel; Agbon, Andrew O.; Agbo, Stanley O.; Waidi, Abdul O.; Tunde, Omoniyi (FUDMA Journal of Sciences, 2026)
The African continent continues to face challenges in improving water accessibility, exacerbated by significant water quality issues that pose serious risks to public health, particularly through the transmission of waterborne diseases. This study aimed to evaluate the Water Quality Index (WQI) of Egbe Reservoir, a crucial source of potable water and irrigation for several local governments in Ekiti and Ondo states in Southwestern Nigeria. The assessment utilized selected physicochemical criteria, analyzed through conventional laboratory techniques. Data collected were subjected to statistical analysis using SPSS (Version 25), and the WQI was calculated based on the average of nine chosen variables, following the drinking water standards established by the World Health Organization. The physicochemical analysis of Egbe Dam revealed a generally healthy aquatic environment; however, some sampling stations exhibited signs of pollution, particularly concerning E. coli levels, phosphate (PO4) concentrations (8.33 ± 1.50 mg/L), and nitrate (NO3) concentrations (2.18 ± 1.05 mg/L), which exceeded both national and international standards. The WQI showed a weak positive correlation with temperature (0.452) and strong negative correlations with total phosphate (-0.925) and E. coli (-0.706), indicating that improved water quality is linked to lower levels of these contaminants. The overall WQI for Egbe Reservoir was 83.05, with the Ode station scoring the highest at 91.25, indicating good water quality, while the lowest score of 57.58 at Downstream still categorized as good.